Environmental DNA reveals protist biodiversity in mangrove sediments of Java and Madura, Indonesia - MIRZA HANIF AL FALAH; TRI RETNANINGSIH SOEPROBOWATI; HADIYANTO HADIYANTO; AULIA RAHIM; JUMARI JUMARI; LILIH KHOTIMPERWATI; NI KADEK DITA CAHYANI; MARTA WOJEWÓDKA-PRZYBYŁ; ŁUKASZ KRUSZEWSKI; PAWEŁ RYDELEK (Society for Indonesian Biodiversity, 2025)
Abstract. Al Falah MH, Soeprobowati TR, Hadiyanto H, Rahim A, Jumari J, Khotimperwati L, Cahyani NKD, Wojewódka-Przybyl M, Kruszewski L, Rydelek P. 2025. Environmental DNA reveals protist biodiversity in mangrove sediments of Java and Madura, Indonesia. Biodiversitas 26: 5211-5225. Mangrove ecosystems provide critical ecological services and harbor diverse microbial communities; however, the diversity of protists and their ecological roles in these habitats remains understudied. This research investigated the protist community composition in mangrove sediments from seven sites across the Java and Madura Islands, Indonesia, using environmental DNA (eDNA) metabarcoding targeting the 18s rRNA gene. Sediment samples were analyzed via Illumina MiSeq sequencing, with taxonomic assignment performed using the PR2 database. Five major protist supergroups were detected, exhibiting significant site-specific variations in community structure. Additionally, a wide range of taxa at the genus and species levels, including microalgae, vegetation, fish, insects, amoebae, protists, nematodes, fungi, and merostomata, were identified. The detection of parasitic and potentially pathogenic taxa, such as Exobasidiomycetes and Malassezia globosa, highlights potential ecological risks in mangrove sediments. The presence of diverse protists and fungi indicates active nutrient cycling and ecosystem resilience. Water quality supports the ecological function of mangrove habitats, with Total Dissolved Solids influencing the abundance of Malassezia globosa and Tetrahymena. This study demonstrates that eDNA metabarcoding is a novel method for revealing hidden biodiversity that is often missed by traditional methods. These findings provide crucial baseline data for the conservation and sustainable management of mangrove habitats, contributing to informed restoration and environmental monitoring efforts that protect vital ecosystem services in coastal regions.